Analisis Hukum Wadh'i dalam Ushul Fiqih - Rindi R; Ahmad Akhyar Syahrir; Hidayat Nurwahid; Besse Ruhaya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Wad'i law is an essential component of Usul al-Fiqh that explains the conditions, requirements, causes, and impediments determining the applicability of taklifi rulings. Understanding Wad'i law serves as the foundation for the proper implementation of Islamic law, as it clarifies when and under what circumstances a particular legal ruling becomes applicable. This study aims to examine the concept, legal foundations, classifications, and the perspectives of the four major schools of Islamic jurisprudence regarding the application of Wad'i law. The study employs a library research method with a descriptive-analytical approach by examining the Qur'an, the Sunnah, classical and contemporary Usul al-Fiqh literature, and other relevant scholarly sources. The findings reveal that Wad'i law consists of divine rulings that establish something as a cause (sabab), condition (shart), impediment (mani'), validity (sahih), invalidity (fasid/batil), and, according to some scholars, also includes 'azimah (original ruling) and rukhsah (legal concession). The foundations of Wad'i law are derived from the Qur'an, the Sunnah, and the principles of Usul al-Fiqh, which explain the relationship between causes, conditions, and impediments in determining legal rulings. Furthermore, differences exist among the Hanafi, Maliki, Shafi'i, and Hanbali schools concerning the application of several aspects of Wad'i law, particularly regarding the conditions for the validity of acts of worship and the determination of legal causes. Therefore, Wad'i law plays a strategic role as a legal framework that explains the mechanism for implementing taklifi rulings, ensuring that Islamic law is applied correctly, proportionately, and in accordance with the provisions established by the Sharia.